2021
DOI: 10.4149/neo_2020_200325n307
|View full text |Cite
|
Sign up to set email alerts
|

Combination of metformin and cold atmospheric plasma induces glioma cell death to associate with c-Fos

Abstract: Glioma is the most common type of brain cancer. Chemotherapy combination with surgery and radiotherapy is a standard treatment for patients. Although there are many advances in glioma therapy, the prognosis of glioma patients has not significantly been improved over the past decades. Hence, there is still an urgent need to develop a new therapy to treat glioma. Cell viability was assessed by CellTiter Blue assay; flow cytometry (FCM) was used for detecting cell apoptosis; ROS detection was detected by ROS Assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Previous studies have shown the effectiveness of CAP jet in inducing RONS accumulation in brain cancer cells without affecting normal cells [43][44][45][46][47][48]. The anti-cancer properties of CAP can be attributed to RONS as CAP generated RONS blocked PI3K/AkT pathway, downregulated JNK and ERK1/2 signaling and activated p53, caspase-3 & 7 and PARP leading to apoptosis in brain cancer cells [44].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies have shown the effectiveness of CAP jet in inducing RONS accumulation in brain cancer cells without affecting normal cells [43][44][45][46][47][48]. The anti-cancer properties of CAP can be attributed to RONS as CAP generated RONS blocked PI3K/AkT pathway, downregulated JNK and ERK1/2 signaling and activated p53, caspase-3 & 7 and PARP leading to apoptosis in brain cancer cells [44].…”
Section: Discussionmentioning
confidence: 97%
“…Intracranial CAP jet treatment inhibits tumor growth in glioblastoma bearing mice [45]. Furthermore, combination of metformin and CAP showed synergistic anti-cancer effects in glioma cell lines U251 and U87 [47].…”
Section: Discussionmentioning
confidence: 98%
“…However, only 4 and 2 genes, respectively, were found commonly regulated by H 2 O 2 and CAP, indicating that non-ROS constituents are responsible for the regulation of the majority of CAP-regulated genes, including both PTGER3 and HSPA6 [ 67 ]. CAPs also deregulate the expression of several transcription factors, including c-FOS [ 68 ] and Yes-associated protein YAP/transcriptional enhancer associated domain TEAD [ 29 ]. In MCF-7 breast cancer cells, up and downregulation of ZNRD1 gene (DNA directed RNA-polymerase 1 subunit) correlated with long and short CAP treatment scheme.…”
Section: Intercellular Effects Of Reactive Species Generated By Camentioning
confidence: 99%
“…cisplatin, metformin) in colorectal cancer, glioblastoma, oral squamous cell carcinoma, glioma cells, and others. [53][54][55][56] CAP is extensively praised for its selective cancer targeting via ROS-mediated oxidative stress. However, in contrast, it is also essential to consider that CAP induced massive ROS formation extracellularly.…”
Section: Combination Of Sulfasalazine and Cap Enhances Cell Deathmentioning
confidence: 99%